Learning Mathematics On Number Patterns Using Tile Arrangement Context To Improve Students' Learning Outcomes - Dedi Yansen (Sean Institute, 2025)
This research aims to improve student learning outcomes through the application of mathematics learning in the context of tile arrangements in number pattern material. The research subjects were students of class VIII SMP Yayasan Bakti Prabumulih . The method used in this research is Classroom Action Research (PTK) which consists of two cycles. Each cycle includes planning stages, action implementation, observation and reflection. Data was obtained through learning results tests, observations and interviews. The research results show that the use of tile arrangement contexts in learning number patterns can improve student learning outcomes, as indicated by an increase in the average student score in each cycle. In Cycle I, only 25% of students completed and 50% were actively involved in learning. In Cycle II, students who completed increased to 85% and students who were active in learning increased to 80%